TRAINING MODEL TO INCREASE EMPLOYEE WORK PRODUCTIVITY - Dalimunte, Aldrin; Marhalinda, Marhalinda; Moeins, Anoesyirwan (Dinasti International Journal of Management Science, 2021)
The objectives of this study are as follows: To determine the level of influence of the implementation of existing education and training programs on employee productivity. Based on the data processing results, it is known that the elements of the implementation of education and training programs that must be considered and improved are as follows: Training Materials, Non-Formal Education, Training Schedules, Instructor Friendly, Training Variations, Training Methods, and Training Manual Books. Meanwhile, the elements of implementing education and training programs that must be maintained are as follows: Formal Education, Instructor Skills, Instructor Ability, Training Facilities, Training Curriculum, Training Evaluation. The implementation of education and training programs affects employee work productivity, and the implementation of training programs is more dominant. This is because the implementation of training programs is carried out more often and is more applicable even though it still seems theoretical on employees' work. Therefore, the right education and training program will impact increasing the productivity of its employees.